STRATEGI PEMASARAN DIGITAL UMKM KULINER DI ERA MEDIA SOSIAL - Hakim, Muhamad Rachman; Abdillah, Khoiruddin; Sitinjak, Gabriel Asoloan; Prasetyoningtyas, Ari Anggarani Winadi (Penerbit Widina, Widina Media Utama, 2025)
The rapid development of digital technology has transformed the marketing landscape for Micro, Small, and Medium Enterprises (MSMEs), particularly in the culinary sector. Social media has become not only a communication platform but also a strategic tool for building brand identity, expanding market reach, and strengthening customer relationships. This article aims to analyze digital marketing strategies that can be applied by culinary MSMEs in the social media era through literature review and conceptual analysis. The results of this study indicate several relevant strategies, namely brand identity and storytelling, creating creative and interactive content, collaboration with influencers, enhancing customer engagement, and utilizing paid advertising. Nevertheless, culinary MSMEs still face several challenges, such as limited digital literacy, restricted promotional budgets, and intense market competition. On the other hand, significant opportunities are offered through short-video content trends, the optimization of WhatsApp Business, and the use of analytics tools for evaluating marketing performance. With the implementation of appropriate and consistent digital marketing strategies, culinary MSMEs have the potential to increase competitiveness, expand their markets, and establish long-term relationships with customers.ABSTRAK Perkembangan teknologi digital telah mengubah lanskap pemasaran bagi Usaha Mikro, Kecil, dan Menengah (UMKM), khususnya sektor kuliner. Media sosial tidak hanya menjadi sarana komunikasi, tetapi juga instrumen strategis untuk membangun merek, meningkatkan jangkauan pasar, dan memperkuat hubungan dengan konsumen. Artikel ini bertujuan untuk menganalisis strategi pemasaran digital yang dapat diterapkan UMKM kuliner di era media sosial melalui kajian literatur dan pendekatan konseptual. Hasil kajian menunjukkan bahwa terdapat beberapa strategi kunci yang relevan, yaitu pembangunan identitas merek dan storytelling, penciptaan konten kreatif dan interaktif, kolaborasi dengan influencer, peningkatan keterlibatan konsumen (customer engagement), serta pemanfaatan iklan berbayar. Meskipun demikian, UMKM masih menghadapi hambatan berupa keterbatasan literasi digital, modal promosi, dan persaingan pasar yang ketat. Di sisi lain, peluang besar terbuka melalui tren video pendek, optimalisasi WhatsApp Business, serta pemanfaatan data analitik untuk evaluasi strategi. Dengan penerapan strategi pemasaran digital yang tepat dan konsisten, UMKM kuliner berpotensi meningkatkan daya saing, memperluas pasar, serta menciptakan hubungan jangka panjang dengan konsumen.